Negative communication in psychosis: understanding pathways to poorer patient outcomes. - Finnegan, D; Onwumere, J; Green, C; Freeman, D; Garety, P; Kuipers, E (Lippincott Williams and Wilkins, 2014)
High expressed emotion (EE) is a robust predictor of elevated rates of relapse and readmission in schizophrenia. However, far less is known about how high EE leads to poorer patient outcomes. This study was designed to examine links between high EE (criticism), affect, and multidimensional aspects of positive symptoms in patients with psychosis. Thirty-eight individuals with nonaffective psychosis were randomly exposed to proxy high-EE or neutral speech samples and completed self-report measures of affect and psychosis symptoms. Patients reported significant increases in anxiety, anger, and distress after exposure to the proxy high-EE speech sample as well as increases in their appraisals of psychosis symptoms: voice controllability, delusional preoccupation, and conviction. These findings offer further evidence of the potential deleterious impact of a negative interpersonal environment on patient symptoms in psychosis.